A dessacralização do cânone: D. João e Julieta e o olhar feminino de Natália Correia - Oliveira, Andrezza Jaquier Pigozzo de (Universidade Federal de São Carlos, 2018)
This monography aims to analyze the play D. João e Julieta, by the Portuguese writer Natália Correia (1923-1993), to, from there, reflect on authorship writing feminine in the Portuguese dramaturgical space, where the presence of women is still difficult and undervalued. Therefore, the choice of work is symptomatic, since, in it, we find the alteration of a social order established by the patriarchy, through a rereading and a deconstruction of tradition, centered, above all, on the Don Juan character image. With this, the proposed reading highlights the desacralizing gesture and the female perspective of the author by revisiting and recreating two figures from the theatrical universe: Don Juan and Julieta.
The desacralization of the canon: D. João and Julieta and the feminine perspective of Natália Correia
Keywords: Dessacralização; Cânone; Teatro português do século XX; Natália Correia; Desacralization; Canon; Portuguese 20th century theater; LINGUISTICA, LETRAS E ARTES::LETRAS::OUTRAS LITERATURAS VERNACULAS